Experiences of Teaching an English for Specific Purposes Course to Students with Disabilities - Barrantes Torres, Daniela (2016)
To complete the master’s program in Teaching English as a Foreign Language at the University of Costa Rica, the teachers designed and taught an ESP course for ten students enrolled in a master’s program in Disability Studies. Three learners have visual impairments, and one has hypoacusis. Different curricular accommodations were made for them to work autonomously, but the results show that some could not always do so. However, their attitude towards learning English improved. This paper presents the challenges and outcomes of the lessons and materials used to raise awareness about the importance of inclusive classes, as well as recommendations to work with this population.